2009
DOI: 10.1021/jm900597q
|View full text |Cite
|
Sign up to set email alerts
|

RNase H Active Site Inhibitors of Human Immunodeficiency Virus Type 1 Reverse Transcriptase: Design, Biochemical Activity, and Structural Information

Abstract: Pyrimidinol carboxylic acids were designed as inhibitors of HIV-1 RNase H function. These molecules can coordinate to two divalent metal ions in the RNase H active site. Inhibition of enzymatic activity was measured in a biochemical assay, but no antiviral effect was observed. Binding was demonstrated via a solid state structure of the isolated p15-Ec domain of HIV-1 RT showing inhibitor and two Mn(II) ions bound to the RNase H active site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
114
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 28 publications
7
114
1
Order By: Relevance
“…The pocket's proximity to the NNRTI pocket may be useful for the structure-based design of new NNRTIs. During the preparation of this report, two structures of inhibitors bound to the HIV RNase H active were published (15,18). Despite the differences between the pyrimidal carboxylic acid scaffold that was described by Kirshberg et al, the betathujaplicinol described by Himmel et al, and the naphthyridinones described herein, all of the inhibitors appear to use two metal ions to coordinate the inhibitor with the active site residues.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The pocket's proximity to the NNRTI pocket may be useful for the structure-based design of new NNRTIs. During the preparation of this report, two structures of inhibitors bound to the HIV RNase H active were published (15,18). Despite the differences between the pyrimidal carboxylic acid scaffold that was described by Kirshberg et al, the betathujaplicinol described by Himmel et al, and the naphthyridinones described herein, all of the inhibitors appear to use two metal ions to coordinate the inhibitor with the active site residues.…”
Section: Discussionmentioning
confidence: 91%
“…This site is located ϳ50 Å from the active site of the RNase H domain. During the preparation of the present study, two reports were published with inhibitors bound to the RNase H active site (15,18).…”
mentioning
confidence: 99%
“…However, the recent approval of boceprevir and telaprevir for the hepatitis C virus NS3-4A serine protease demonstrates that effective small molecules can be designed for shallow binding sites (34 -36). We and others have demonstrated that competition with the nucleic acid substrate is a related potential obstacle in this context (10,23,31). Order-of-addition experiments revealed that ␤-thujaplicinol does not bind to a pre-formed complex composed of HIV-1 RT and substrate (10).…”
Section: Discussionmentioning
confidence: 92%
“…As such, these compounds are generally referred to as active site RNase H inhibitors. Crystal structures of HIV-1 RT RNase H with a bound active site inhibitor confirmed that these compounds are anchored at the RNase H active site and interact with the bound divalent metal ions (22)(23)(24)(25). Allosteric RNase H inhibitors can bind in the vicinity of the polymerase active site as shown for N-acyl hydrazones (26,27), or in the vicinity of the p51 thumb subdomain as shown for vinylogous ureas (28,29).…”
mentioning
confidence: 87%
“…Since the RNase H function is essential for viral replication (5), it has been explored as a drug target, and a number of RNase H inhibitors (RHIs) have been reported (6)(7)(8). RHIs can be classified based on their binding sites, i.e., (i) RHIs that coordinate the two Mg 2ϩ catalytic cofactors at the RNase H active site, such as N-hydroxyimides (9), hydroxytropolones (10), hydroxypyrimidines (11), naphthyridinones (12), nitrofuran-2-carboxylic acid carbamoylmethyl esters (13), hydroxyquinolinones (14), and thiocarbamates and triazoles (15), or (ii) allosteric RHIs, such as vinylogous ureas (16), thienopyrimidinones (17), hydrazones (18), anthraquinones (19), isatines (20,21), and propenones (22).…”
mentioning
confidence: 99%